Social Resilience Psychoeducation: Efforts to Strengthen the Psychosocial Well-being of Beneficiaries at the Panti Pelayanan Sosial PGOT Mardi Utomo Semarang - Novi Qonitatin; Endang Sri Indrawati; Nailul Fauziah; Erin Ratna Kustanti; Adi Dinardinata (ABISATYA : Journal of Community Engagement, 2026)
Beneficiaries (Penerima Manfaat or PM) at social rehabilitation centers encounter multifaceted psychosocial challenges, notably internalized stigma and diminished self-confidence, which hinder their social reintegration despite their vocational skills. Addressing this issue is imperative to avert the “revolving door” phenomenon, wherein beneficiaries return to the streets due to insufficient psychosocial preparedness. This Community Service initiative sought to enhance social resilience among beneficiaries at PPS PGOT Mardi Utomo Semarang through a structured psychoeducation intervention. The program employed a mixed-methods design, utilizing Focus Group Discussions (FGD) to assess baseline dynamics and the Connor-Davidson Resilience Scale (CD-RISC) in a pre-test/post-test design to measure changes following a session on self-efficacy, life purpose, and social support. Qualitative results indicated that while participants possessed knowledge of coping strategies, they were hindered by a lack of self-efficacy; meanwhile, quantitative findings showed no significant increase in resilience scores due to a 'ceiling effect' where 78.6% of participants already scored high at baseline. Consequently, the intervention successfully identified that the core barrier is not a lack of resilience knowledge but a deficit in the confidence to act. It is concluded that future community interventions must shift from knowledge-based psychoeducation to action-oriented programs that build mastery experiences to effectively support this population.